KAJIAN KESESUAIAN KONSERVASI MANGROVE DI PESISIR PANTAI NAMASERU DAN NAMAEA NEGERI PELAUW KABUPATEN MALUKU TENGAH - Maureen Alise Tuapattinaja; Reinhardus Pentury; Frederik Willem Ayal (Universitas Pattimura, 2023)
The mangrove forest ecosystem in Indonesia is currently in a critical state, with approximately 68% or 5.9 million hectares of the total 8.6 million hectares experiencing damage. Various approaches have been taken to reduce this damage and preserve the existence of mangrove forests in Indonesia. One such approach is through extensive conservation efforts, including those in the mangrove forest areas of Namaea and Namaseru coastal, Negeri Pelauw, Central Maluku Regency. This research aims to: 1) identify and analyze the potential of mangrove forests; 2) measure the physical-chemical parameters supporting the mangrove ecosystem; and 3) analyze the suitability of mangrove forest conservation development. The analysis stages of mapping the mangrove forest areas in this research begin with the determination of observation stations and data collection, followed by biophysical analysis. The data collected in this study are related to suitability indicators for mangrove conservation based on criteria from Wardhani (2011), Hutabarat (2009), and Khomsin (2005). The research conducted in Namaseru coastal found 16 mangrove species, while in Namaea coastal, 14 mangrove species were identified. The physical-chemical parameters supporting the Negeri Pelauw mangrove ecosystem, including water temperature, salinity, substrate type, slope, distance from freshwater sources/rivers, tidal height, pH, and current, are still within ranges conducive to mangrove forest growth. The suitability index for conservation area development in Namaea coastal is categorized as Very Suitable (S1), and in Namaseru coastal, it is categorized as Suitable (S2).